2023
DOI: 10.1021/acs.macromol.2c02582
|View full text |Cite
|
Sign up to set email alerts
|

Through-Space Charge-Transfer Thermally Activated Delayed Fluorescence Alternating Donor–Acceptor Copolymers for Nondoped Solution-Processable OLEDs

Abstract: A series of donor−acceptor alternating copolymers with M n ≤ 12,000 g mol −1 and moderate polydispersity (Đ = 1.5− 2.5) were synthesized via RAFT copolymerization of styrene-based donor monomers and maleimide-type acceptor monomers in the presence of S-dodecyl-S′-(α,α′-dimethyl-α″-acetic acid)trithiocarbonate as a chain transfer agent. It was shown that synthesized alternating copolymers were characterized by high thermal stability (T d5 = 375−465 °C), and most of them exhibited exciplex emission via the throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
(136 reference statements)
0
5
0
Order By: Relevance
“…Significant AIE activity was again observed in the TSCT polymers containing acridan donor and triarylboron acceptors, synthesized by the same group. , These results indicated that the aggregation of the polymer chains may faciliate the excited state emission from the TSCT processes that are dependent on the D–A distance. In a recent study, another type of TSCT polymer was synthesized by alternating copolymerization of styrenic donor monomers and maleimide-derived acceptor monomers. AIE properties were also reported in these polymers, which further confirmed the aggregated-enhanced TSCT effect.…”
Section: Monomeric D–a Tsctmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant AIE activity was again observed in the TSCT polymers containing acridan donor and triarylboron acceptors, synthesized by the same group. , These results indicated that the aggregation of the polymer chains may faciliate the excited state emission from the TSCT processes that are dependent on the D–A distance. In a recent study, another type of TSCT polymer was synthesized by alternating copolymerization of styrenic donor monomers and maleimide-derived acceptor monomers. AIE properties were also reported in these polymers, which further confirmed the aggregated-enhanced TSCT effect.…”
Section: Monomeric D–a Tsctmentioning
confidence: 99%
“…Overall, polymerization has been used as a robust and convenient tool to manipulate the donor-to-acceptor TSCT in the manner of monomer-to-monomer , (including side chain-to-side chain), end group-to-initiator, and monomer-to-initiator modes . By rational structural design, more diverse polymeric TSCT systems remain to be discovered based on the controlled polymerization-mediated TSCT strategy.…”
Section: Monomer (D)-to-initiator (A) Tsctmentioning
confidence: 99%
“…Kostjuk et al demonstrated the synthesis of 16 new styrene-based donor–acceptor alternating copolymers ( D1A1 to D4A4 ) for use as non-doped TADF emitters (Scheme 6). 66 These polymers were created through reversible addition–fragmentation chain-transfer (RAFT) copolymerization, resulting in an average molecular weight ( M n ) of approximately 12 000 g mol −1 and a moderate polydispersity index (PDI) ranging from 1.5 to 2.5. The donor monomers included styrene-based 6-dimethoxycarbazole, 9,9-dimethylacridane, and phenoxazine, whereas the acceptor monomers consisted of maleimide-tethered benzophenone and benzonitrile.…”
Section: Nonconjugate Linker-based Tsct Tadf Emittersmentioning
confidence: 99%
“…Molecules exhibiting TSCT, particularly those based on nonconjugated spacers, have considerable advantages. 49–77,90–99 These spacers disrupt the direct conjugation between donors and acceptors; thus, they are sophisticated in creating blue emitters and high triplet energy ( E T ) host materials. The use of various nonconjugate spacers, such as adamantane, 67,68 silane (Si), 69 cyclohexane, 62–65,70,71 vinyl, 75–77 and others, 52–61 offers a diverse toolkit for tailoring the properties of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it typically results in inevitable red-shifted emission and even the absence of TADF property. Thanks to the efforts of researchers, a series of different kinds of nonconjugated alternating copolymers with poly­(maleic anhydride- alt -styrene), , poly­(maleimide- alt -styrene), , and poly­(maleic anhydride- alt -vinyl acetate) skeletons were successfully developed . Benefiting from this accurate sequence structure, the well-defined alternating copolymers exhibit advantageous properties such as the enhanced thermal stabilities and unexpectedly luminescent properties. Unlike the random structures in conventional TSCT-based TADF copolymers, alternating polymerization would be more powerful to construct sequence-controlled alternating copolymers. , …”
Section: Introductionmentioning
confidence: 99%